Features of intersectoral collaboration in the field of public health at the local level - Manshina, A; Popovich, M V; Zinovieva, V A (European journal of public health, 2020)
Background Studying the characteristics of intersectoral collaboration (IC) of representatives of various sectors in the development and implementation of programs for the prevention of noncommunicable diseases and the formation of a healthy lifestyle in the constituent entities of the Russian Federation (RF). Methods Studying the opinions of representatives of various sectors on IC in the development and implementation of programs for the prevention of NCDs and the formation of a healthy lifestyle in four regions of the RF by interview. Identification of factors contributing to and hindering intersectoral interaction at the local level. Results In total, 43 interviews were conducted with representatives: municipal administrations, the public chamber, trade unions, non-profit organizations, departments of health, sports, culture, education, social protection, Labor and Employment, Federal Service for Oversight of Consumer Protection and Welfare. Factors contributing to IC: the presence of a coordination council; Support from the management of the entity; joint solution of tasks, the presence of horizontal links between departments and organizations involved in political decisions. Factors hindering IC: lack of a coordinating council; lack of a clear understanding of the tasks for which each agency is responsible and what results need to achieve in the end. Inadequate involvement of public non-profit organizations. Conclusions Intersectoral work is underway in the regions, in all the subjects surveyed, horizontal ties have been established between departments and organizations involved in making political decisions or influencing them. All participants recognize the importance and necessity of intersectoral work in the form of a council (commission). For effective intersectoral work, it is necessary to determine priorities in joint work, delimit areas of responsibility between participants, establish tasks that need to be achieved and performance determine criteria. Key messages Studying the characteristics of intersectoral collaboration (IC) of representatives of various sectors in the development and implementation of programs for the prevention of noncommunicable diseases. To ensure intersectoral work, it is necessary to determine priorities in joint work, delimit areas of responsibility, establish tasks and determine performance criteria.